Trust Based Cloud Service Provider Selection (International Journal of Engineering and Computer Science, 2017)
With the new emerging technologies the cloud marketplace has identified many new cloud service providers which provide a similar service and offerings. The services and offerings are provided in an agreement named as Service Level Agreement (SLA).The SLA is the agreement that has been established between the providers and the users. The services provided in the SLA by the providers are not consistent and satisfiable for the consumers. The environment like a cloud, the quality of service is said to be a very important parameter. In order to reduce the inconsistency of SLA it proposes Trust Based Cloud Service Provider Selection which provides the scalable and reliable cloud service providers to the consumers. In the proposed work the trust value is estimated with the interaction between the users and the providers. With the help of the ratings provided to the cloud service providers’ by the users, the trustworthiness is estimated by confidence level, which is determined by the recent interaction and the interaction intensity. The competence is estimated by the parameters like security, availability, policies provided by the providers to the users. The trustworthiness and competence are combined to find the cloud service providers of user needs and the performance is estimated.